Research on Evaluation of Linux in Aerospace Based on Improved FAHP. Issue 5 (June 2019) - Yu, Su; Yushuai, Liu; Li, Sun; Zhexi, Yao; Jinbo, Wang
Abstract: The evaluation and selection of embedded operating system are very important for manned spaceflight engineering. Considering the fuzziness and hierarchy of the evaluation process, a fuzzy analytic hierarchy process (FAHP) based on variation coefficient method and Criteria Importance Though Intercrieria Correlation (CRITIC) method is proposed to be applied to comprehensive evaluation of real-time Linux in space embedded system. The evaluation system, evaluation set and Gaussian distribution membership function are constructed, and the weight values of each criterion and index are determined by variation coefficient method and CRITIC method. The measured data are used for quantitative indexes such as real-time performance, and the expert scoring method is used for qualitative indexes such as reliability and compatibility, and verifies the validity of the model through simulation. The results show that the improved FAHP can quickly and intuitively judge the performance characteristics of Linux system and its derivatives, and provide a method for scientific and effective evaluation of space embedded operating system.